Investigating the relationship between lecturer’s occupational stresses and commitments to organization - Tran, Thị Cẩm Tú; Truong , Quang Được (Journal of Technical Education Science, 2015)
The objective of this study was to investigate the influence of occupational stresses on lecturers’ commitment to their organizations. An online survey was applied to collect data from 244 lecturers in Ho Chi Minh City to test the hypotheses. Exploratory factor analysis (EFA) and multiple regressions were the two major statistical approaches used for scale purification and data analysis. Result have shown that five occupational stressors such as: work relationship, career development opportunities, workload, incomes and benefits, and student- related issues do affect on the commitment of lecturers to their institutions. This research is a meaningful ref-erence for university, institute faculty members in Viet Nam.